Logistics centers location - Klapita, Vladimír; Švecová, Zuzana (Transport, 2006)
It is fairly questionable to estimate future costs in the problems of strategic decision. The uncertainty may cause a resulting solution to be very inefficient considering current costs. In this report we try to find an approach which enables to determine a unique solution of a location problem at uncertain costs so that the solution is resistant to future changes. We deal with a sensitivity analysis and with a connection of an exact mathematical programming method and the theory of fuzzy sets. First Published Online: 27 Oct 2010